Analysis of scores differences in the ENLACE test between boys and girls in the Mexican school system - Campos Vázquez, Raymundo M.; Santillán Hernández, Alma S. (Estudios Económicos de El Colegio de México, 2016)
This paper analyzes the gender gap in standardized test scores in Mexico. The data used comes from the ENLACE test for primary, junior high and high school. In primary and junior high school, girls perform better than boys in both spanish and math across the test score distribution, but in the top part of the math score distribution. In high school, across the test score distribution, girls perform better than boys in spanish and the opposite occurs in math.